Correlação de sedimentos e eventos chuvosos em um trecho do rio Santa Maria da Vitória - ES - Rampinelli, Fabiana Giacomin (2013)
The Santa Maria da Vitória River basin presents sediment production resultant from the interaction of many hydro-geological processes. This basin it is one of the most important basins for the Espírito Santo state because it supplies water for most of the its metropolitan region provision. The main objective of the dissertation is verify the existence of a correlation between suspended sediments transport and rains, campaigns in three different sections were realized between Rio Bonito and Suiça s reservoirs. The campaigns showed that low quantity of sediments remains in the deep of the reservoir and it has a bigger grain size. The results also proved that there is no correlation between the mean of rains in the basin and the sediments concentration, indicating that the great size of the basin contributes for the distribution of the values. The sediments, when related with stream flow in rainy days, presents high values and daily basis sediments collections and stream flow analysis demonstrated that rains may not be noticed immediately in the section. When the grain distribution is analyzed, they presented medium sizes, predominantly, in the deep samples and fine size, predominantly, in the suspended ones. The total discharge values of sediment were overestimated by using the Einstein method, modified by Colby. However, it can be noticed low solids discharges in the section located upstream hidroeletric Suíça, which can be related to the existence of the Rio Bonito dam that should occur sediments deposition from the water course